Nanoplasmonic Biosensing for Soft Matter Adsorption: Kinetics of Lipid Vesicle Attachment and Shape Deformation - Zhdanov, Vladimir P. (2016)
An indirect nanoplasmonic sensing platform is reported for investigating the kinetics of attachment and shape deformation associated with lipid vesicle adsorption onto a titanium oxide-coated substrate. The localized surface plasmon resonance (LSPR) originates from embedded gold nanodisks and is highly sensitive to the local lipid environment. To interpret the corresponding results, we have extended treatments of diffusion-limited adsorption kinetics and adsorbate-related LSPR physics, identified the expected scaling laws for the LSPR-tracked kinetics measured at different lipid concentrations and/or nanometer-scale vesicle sizes in the case when vesicle deformation is negligible, and scrutinized experimental deviations accordingly. After adsorption, the smallest 58 nm diameter vesicles were found to maintain shape on the time scale of adsorption at high lipid concentrations in solution, and shape deformation became more appreciable at lower lipid concentrations. Higher saturation coverage was observed with increasing lipid concentration, which is attributed to the difference in relative time scales of vesicle attachment and deformation. For larger vesicles between 80 and 160 nm diameter, deviations associated with their shape deformation and correlations with the location of gold nanodisks became more apparent at moderate and high coverages. Taken together, the results obtained support that the quantitative measurement capabilities of nanoplasmonic biosensing should be considered for applications demanding highly surface-sensitive characterization of soft matter adsorption and related phenomena at liquid–solid interfaces.